Impact of beta blockers on cancer neuroimmunology: a systematic review and meta-analysis of survival outcomes and immune modulation - Zhang, Fangyuan; Wang, Yu; Liu, Feng; Li, Yixian; Liu, Xinxin; Ren, Xueying; Yuan, Xi (Frontiers in Immunology, 2025)
BackgroundEmerging evidence suggests that beta-blockers (BBs) may influence cancer progression by modulating the neuroimmune axis. However, clinical findings remain heterogeneous, necessitating a comprehensive evaluation of their impact on survival outcomes and immune modulation across malignancies.MethodsWe conducted a systematic review and meta-analysis following PRISMA guidelines, analyzing 79 studies from PubMed, Embase, and Web of Science. Pooled hazard ratios (HRs) for overall survival (OS) and cancer-specific survival (CSS) were calculated using random-effects models. Subgroup analyses explored effects by cancer type, BB class (non-selective vs. β1-selective), and concurrent immunotherapy. Immune biomarkers (e.g., PD-L1 expression, tumor-infiltrating lymphocytes) were qualitatively synthesized.ResultsBB use showed no significant overall effect on CSS (HR = 0.97, 95% CI: 0.92–1.02) but exhibited substantial heterogeneity (I² = 80%). Protective associations were observed in breast cancer (HR = 0.27–0.50) and melanoma, while detrimental effects emerged in pancreatic and head/neck cancers (HR > 1.0). Clinically, BBs combined with immune checkpoint inhibitors (ICIs) improved survival (HR=0.91, 95% CI: 0.85–0.98), particularly in PD-L1+ tumors (OR=1.29 for enhanced expression). Non-selective BBs showed stronger immune modulation (CD8+ T-cell SMD=0.49 vs 0.22 for β1-selective).ConclusionBBs demonstrate clinically meaningful benefits when combined with immunotherapy (HR=0.91) particularly in β2-AR+ melanoma and breast cancer, but show potential harm in pancreatic/head-neck cancers (HR>1.0). These results support preferential use of propranolol (20-40mg/day) in immunotherapy-treated melanoma, and avoidance of routine BB use in non-immunogenic tumors without adrenergic profiling. Prospective trials should validate these selection criteria.